Clinicopathological and immunohistochemical study of canalicular adenoma - de Vasconcelos Carvalho, Marianne; Arteaga Legarrea, Juan Manuel; Prado Ribeiro, Ana Carolina; Paiva Fonseca, Felipe; Benevenuto de Andrade, Bruno Augusto; Paes de Almeida, Oslei; Ajudarte Lopes, Márcio; Vargas, Pablo Agustin (Journal of Oral Diagnosis, 2024)
Objective: To evaluate the clinicopathological and immunohistochemical features of an original series of canalicular adenoma. Methods: Cases diagnosed as canalicular adenoma from a single center were retrospectively retrieved and clinical data collected from patients’ charts. The histopathological features of all cases were reviewed and a large immunohistochemical panel carried out. Results: Eleven cases were collected, and no gender predilection was seen. A painless upper lip nodule was the most frequent clinical presentation. All cases presented the single-layer epithelial arrangement of tumor cells in a loose stroma. It was found an increased expression of low-weight cytokeratins, absence of myogenic markers, variable positivity for vimentin, S100 and GFAP, cytoplasmic and membrane reactivity for β-catenin and a strong CD34 positivity, whereas no lymphatic vessel was identified using D2-40 antibody. Conclusion: Canalicular adenoma is composed of luminal epithelium with strong expression of low-weight cytokeratins, and peripheral expression of β-catenin may be involved in the architectural maintenance of the tumor.